Avaliação agronômica do amaranto em Lucas do Rio Verde, MT - Pittelkow, Fabio Kempim (2014)
This study consisted of three experiments on Oxisol dystrophic, with the following objectives: i) evaluate the effect of soil compaction on their physical properties, nutrient content in the leaves, root growth and the amaranth yield ii) evaluate the effect of differents times of sowing and densities in the Amaranth yield in soybeans succession; iii) evaluate the effect of increasing phosphorus doses in Amaranth yield in soybeans succession. To meet the first objective, an experiment was conducted in the field experiment with amaranth, at factorial scheme 2X5 and five replications, were two cultivars of amaranth (A. cruentus cv. 'BRS Alegria’ and A. caudatus cv. 'Inca') and five campaction levels (PT0, PT1, PT2, PT4 and PT6 - compacted by tractor traffic in zero, one, two, four and six passes wheelset of an agricultural tractor. The cumulative traffic turned the tractor causes increased bulk density and soil penetration resistance and reduction of soil macroporosity up to 0.10 m depth. Soil compaction reduces foliar nitrogen and potassium, but did not affect the phosphorus content in the leaves of amaranth cv. 'BRS Alegria' and 'Inca'. Increased soil compaction causes an increase in the diameter of amaranth roots. The productivity of amaranth cultivars is low because of soil compaction. For the second objective was conducted a test with Amaranthus cruentus cv. 'BRS Alegria' in a randomized block design with four replications in factorial scheme at 5x4. The first factor it is related to five dates of sowing (16/02/2013; 26/02/2013; 05/03/2013; 20/03/2013 and 04/05/2013) and the second factor the four densities sowing of (106.000, 187.000, 262.000 and 358.00 pl ha-1 ). Water restriction in the A. cruentus cv. 'BRS Alegria' after the issuance of panicle and anthesis process reduces the productive potential of culture. Sowing in late March and early April elevates the protein contents in grains of A. cruentus cv. 'BRS Alegria'. The population density more potential productive A. cruentus cv. 'BRS Alegria' is situated between 228.000 and 242.000 pl ha-1 in spreading performed in February. To meet the third objective was conducted a test with A. cruentus cv. 'BRS Alegria' in soybeans succession with increasing phosphorus doses, in a randomized block design with five treatments (0, 30, 60, 100 and 150 kg ha-1 P2O5 as triple superphosphate) applied in the furrow in pre-sowing, with four replications. Phosphorus in the furrow application increased productivity and the phosphorus content in the leaves of the amaranth cv. 'BRS Alegria' in soybean succession. The greatest estimated yield of amaranth grain is obtained with 98.7 kg ha-1 P2O5 with values very close the level of economic response to application of input.